Historical Process of State and Non-state Media during the Reign of Ghazi Amanullah Khan - Amin, Azizullah; Habibi, Habib Rahman; Wafa, Amanuddin (Randwick International of Social Science Journal, 2025)
When Amanullah Khan declared the country's political independence at the beginning of his reign, Mohammad Wali Khan continued his diplomatic and political efforts all the way to Washington, introducing Afghanistan to the world as an independent country. After the declaration of independence, the country also began to make efforts to strengthen the political and cultural consciousness of its citizens. In addition to achieving other human rights, the Afghan people and the population also obtained the right to freedom of the press and expression by government decision. At the same time, radio and cinema were made available for use. Music education officially began. At the same time, the government officially authorized state and non-state media and established a large number of schools and media outlets to strengthen the political and cultural consciousness of its citizens and populations so that the educational level of the citizens and populations could be increased.